COVID-19 and diabetes: How to manage? - Maskey, R.; Gupta, P.P. (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Patients with diabetes have an increased risk of severe complications including Adult Respiratory Distress Syndrome and multiorgan failure. Depending on the global region, 20–50% of patients in the coronavirus disease 2019 (COVID-19) pandemic had diabetes.